Quality Improvement and Defect Control in Food Packaging Industry with DMAIC Approach - Monica Feby Santoso; M. Nushron Ali Mukhtar (Fakultas Teknik Universitas Tulang Bawang, 2026)
Low product packaging quality in food products can negatively impact customer satisfaction and company performance. This research aims to evaluate and improve the packaging quality of Shanghai Atom Peanut products, with a primary focus on reducing defects through the Six Sigma DMAIC approach. The main objective is to identify the root causes of packaging defects and implement measurable improvement strategies to enhance production process stability. The findings identified two CTQ factors that accounted for 84.3% of total defects: inaccurate product weight and poor sealing quality. Prior to improvement, 814 defective units were found out of 6,480 inspected. As a result, the number of defective units decreased significantly to 299, with all data points falling within control limits. The RPN also showed a substantial reduction, with D1 decreasing from 336 to 175 and D2 from 294 to 100. Statistical analysis using a paired T-test yielded a P-Value of 0.001, indicating a statistically significant improvement. The primary contribution of this research lies in its comprehensive application of all DMAIC phases through to the control stage an approach that is rarely detailed in similar studies within the food packaging industry. This research recommends future evaluations of the DMAIC methodology across various packaging types, such as metallized film, carton boxes, and cans, to support the development of more efficient and adaptability to market-oriented needs. Keywords: DMAIC, Food Industry, Packaging Defect, Quality Control, Six Sigma